Coffee and Tea Consumption Impact on Amyotrophic Lateral Sclerosis Progression: A Multicenter Cross-Sectional Study - Cucovici, Aliona; Ivashynka, Andrei; Fontana, Andrea; Russo, Sergio; Mazzini, Letizia; Mandrioli, Jessica; Lisnic, Vitalie; Muresanu, Dafin Fior; Leone, Maurizio Angelo (Frontiers in Neurology, 2021)
Background/Objectives: Amyotrophic Lateral Sclerosis (ALS) is a devastating and still untreatable motor neuron disease. The causes of ALS are unknown, but nutritional factors may impact the rate of disease progression. We aimed to ascertain the influence of coffee and tea consumption on ALS progression rate. Subjects/Methods: In this multicentre cross-sectional study, we recruited 241 patients, 96 females, and 145 males; the mean age at onset was 59.9±11.8 years. According to El Escorial criteria, 74 were definite ALS, 77 probable, 55 possible, and 35 suspected; 187 patients had spinal onset and 54 bulbar. Patients were categorized into three groups, according to their ΔFS (derived from ALS Functional Rating Scale-Revised score and disease duration from onset): slow (81), intermediate (80), and fast progressors (80). Results: Current coffee consumers were 179 (74.3%), 34 (14.1%) were non-consumers, 22 (9.1%) former consumers, whereas six (2.5%) consumed decaffeinated coffee only. The log-ΔFS was weakly correlated with the duration of coffee consumption (p=0.034), but not with the number of cup-years, or the intensity of coffee consumption (cups/day). Current tea consumers were 101 (41.9%), 6 (2.5%) were former-consumers, and 134 (55.6%) non-consumers. Among current and former consumers, 27 (25.2%) consumed only green tea, 51 (47.7%) only black tea, and 29 (27.1%) both. The log-ΔFS was weakly correlated only with the consumption duration of black tea (p=0.028) but not with the number of cup-years. Conclusions: Our study does not support the hypothesis that coffee or tea consumption is associated with the ALS progression rate.